The Added Burden of Personality Disorder on Subsidized Australian Health Service Utilization Among Women With Mental State Disorder - Kavanagh, Bianca E.; Gwini, Stella M.; Pasco, Julie A.; Stuart, Amanda L.; Quirk, Shae E.; Gaston, James; Holloway-Kew, Kara L.; Turner, Alyna; Berk, Michael; Dean, Olivia M.; Chanen, Andrew M.; Koivumaa-Honkanen, Heli; et al. (Frontiers in Global Women's Health, 2021)
This study aimed to investigate health service utilization among women with mental state disorder only (MSD-PD), mental state disorder plus personality disorder (MSD+PD), and controls in a population-based sample. Women (n = 635) from the Geelong Osteoporosis Study completed mental health assessments and were categorized into groups (MSD-PD, MSD+PD, controls). General practitioner (mental and non-mental health encounters) and specialized mental health service utilization was ascertained from data linkage to the Medicare Benefits Schedule, Australia (01/09/2008-31/12/2012). Negative binomial and binary logistic regression models were employed to assess health service utilization differences between groups. Results indicated that women with MSD+PD had more encounters of non-mental health service utilization than women with MSD-PD and controls. Age significantly modified these relationships: women with MSD+PD and MSD-PD had more encounters of health service utilization at midlife and in the seventh decade of life. No significant differences were found in the frequency of general practitioner mental health service utilization or specialized mental health service utilization between groups. These data suggest that the presence of co-occurring PD is associated with increased health service utilization among women with other common mental health problems. Healthcare providers should be vigilant to the presence of PD when establishing management plans with patients presenting with common mental health problems.